2017
DOI: 10.1038/s41598-017-15533-z
|View full text |Cite
|
Sign up to set email alerts
|

Oral exposure to dibutyl phthalate exacerbates chronic lymphocytic thyroiditis through oxidative stress in female Wistar rats

Abstract: Chronic lymphocytic thyroiditis (CLT) is a common autoimmune disorder. The possible pathogenic role and mechanism of dibutyl phthalate (DBP) in CLT is still controversial. Experiments were conducted after 35-days of oral exposure to the three concentrations of DBP or saline, and three immunizations with thyroglobulin (TG). Healthy female Wistar rats were randomly divided into ten exposure groups (n = 8 each): (A) saline control, (B) 0.5 mg/kg/d DBP, (C) 5 mg/kg/d DBP, (D) 50 mg/kg/d DBP, (E) TG-immunized group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 38 publications
3
13
1
Order By: Relevance
“…A significant negative association was found in the DBP group for the T4 level, as well as in the BPA group. In a study on rats by Wu et al (2017) the decrease in the T3 and T4 levels was demonstrated after five weeks of oral exposure to the same dose of DBP (50 mg/kg/day) [39]. Conversely to our results, the increase in the T4 level was noted in a study in which rats were orally treated with a slightly higher dose of BPA than in our experiment (40 mg/kg b.w.)…”
Section: Thyroid Hormonescontrasting
confidence: 93%
See 3 more Smart Citations
“…A significant negative association was found in the DBP group for the T4 level, as well as in the BPA group. In a study on rats by Wu et al (2017) the decrease in the T3 and T4 levels was demonstrated after five weeks of oral exposure to the same dose of DBP (50 mg/kg/day) [39]. Conversely to our results, the increase in the T4 level was noted in a study in which rats were orally treated with a slightly higher dose of BPA than in our experiment (40 mg/kg b.w.)…”
Section: Thyroid Hormonescontrasting
confidence: 93%
“…On the other hand, our results have demonstrated significantly increased levels of T4 in the MIX group when compared to the control with mixture showing unexpected opposite pattern to the effect of single substances. Similar results were observed in a study in which rats were given the same DBP dose in combination with thyroglobulin immunization [39]. In this study, lower T3 and T4 levels were demonstrated in groups receiving only DBP, while a mixture of DBP and thyroglobulin expressed an opposite effect, a significant increase in these hormones.…”
Section: Thyroid Hormonessupporting
confidence: 89%
See 2 more Smart Citations
“…While there are no data regarding phthalate exposure and RA development, this group of chemicals has been reported to affect other autoimmune diseases. In mice, exposure to dibutyl phthalate aggravated autoimmune thyroid disease andcomparable to our results-induced an increased release of the pro-inflammatory cytokines IL-1β, IL-6, and IL-17 (34,35).…”
Section: Discussionsupporting
confidence: 86%